RFID based inventory management system - Tan, Joshua. (2013)
Radio frequency identification technology is not a recent development. However there is still slow uptake on the use of such technology for various reasons. One such area which would benefit highly from the implementation of such technology would be the inventory management systems. Through careful research, it can be seen that even though there are clear benefits in the implementation of such technology in the area of inventory management systems through studies done is large companies, most companies do not use Radio frequency identification technology to manage their inventory for various reason. As such it is highly beneficial to develop such technologies which are generally applicable to allow various companies to be able to use such technology for their advantage.